Biliary boulders. Issue 3 (8th January 2014) - Steed, H; Lau, K; Glass, R; Durkin, D; Deakin, M; Green, J R B
Abstract : Objective: To examine the outcome of endoscopic retrograde cholangiopancreatography (ERCP) in the management of common bile duct (CBD) stones. Design: A retrospective review of 100 consecutive ERCPs performed for CBD stones. Results: 100 ERCPs were performed on 84 patients with a median cohort age of 77. Completion in this cohort, as defined by duct clearance, was achieved in 65% of cases. Completion rates fell rapidly after two ERCPs. 33% of the cohort had small stones <10 mm, and 67% had stones >10 mm. Size, but not number of stones, affected the completion rate and frequency of complications (16%). Presence of periampullary diverticulum did not affect completion or complication rates. MR cholangiopancreatography (MRCP) had a 90% sensitivity for detecting CBD stones compared with 56% for CT. Discussion and conclusions: ERCP remains a high-risk procedure with a significant complication rate when performed to deal with CBD stones. MRCP should be the second choice of investigation for CBD stones. This cohort had an unusually high number of larger stones at ERCP of 67% compared with other published UK cohorts of 8%, and this was reflected in the completion and complication rate.